Seasonal histomorphology of Acidophils in the Hypophysis cerebri of Gaddi goats: A comparative study between the year 2000 and the present in the context of climate change - RAO, ARJUN KUMAR; PATHAK, VIRENDER; RAJPUT, RAJESH; GUPTA, DIVYA; SHUKLA, PARUL (The Indian Journal of Animal Sciences, 2025)
The present study was conducted to investigate the seasonal histomorphological variations in acidophil cells of the pituitary gland in Gaddi goats, with reference to changing climatic conditions between (2000) and now. A total of 35 heads from adult, pluriparous, non-pregnant Gaddi does were procured from local slaughterhouses in the Palampur region of Himachal Pradesh during different seasons of the year. The pituitary gland, appeared as a light grey, oval or pyriform structure in the interpeduncular fossa. Histological analysis of the pars distalis adenohypophysis revealed significant seasonal differences (P